2016
DOI: 10.1038/ismej.2016.144
|View full text |Cite
|
Sign up to set email alerts
|

The prey’s scent – Volatile organic compound mediated interactions between soil bacteria and their protist predators

Abstract: Protists are major predators of bacteria in soils. However, it remains unknown how protists sense their prey in this highly complex environment. Here, we investigated whether volatile organic compounds (VOCs) of six phylogenetic distinct soil bacteria affect the performance of three different soil protists and how that relates to direct feeding interactions. We observed that most bacteria affected protist activity by VOCs. However, the response of protists to the VOCs was strongly dependent on both the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 20 publications
(26 reference statements)
6
113
0
1
Order By: Relevance
“…In soil, predation pressure on bacteria is likely to be stronger since this environment is known to harbour a huge taxonomic and functional diversity of protist predators and nematodes (Ekelund and Rønn 1994). Protist species are known to differ in their feeding specificity (Schulz-Bohm et al 2016) and it has been shown that a higher predator diversity reduces the strength of competition and increases bacterial diversity (Saleem et al 2012). Moreover, we found a negative correlation between abundance in the absence of predation and abundance reduction in the presence of predators for both rare species groups, but not for the abundant groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In soil, predation pressure on bacteria is likely to be stronger since this environment is known to harbour a huge taxonomic and functional diversity of protist predators and nematodes (Ekelund and Rønn 1994). Protist species are known to differ in their feeding specificity (Schulz-Bohm et al 2016) and it has been shown that a higher predator diversity reduces the strength of competition and increases bacterial diversity (Saleem et al 2012). Moreover, we found a negative correlation between abundance in the absence of predation and abundance reduction in the presence of predators for both rare species groups, but not for the abundant groups.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our hypothesis, the AbunFas group was only weakly affected by predation at all nutrient concentrations. Toxin and volatile production by species belonging to the genera Pseudomonas, Paenibacillus and Bacillus might have enhanced their resistance to predation (Jousset et al 2009, Schulz-Bohm et al 2016). However, these interactions are highly species-and compound-specific (Schulz-Bohm et al 2016) and are therefore beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…By testing various volatile-mediated interactions between phylogenetically different soil bacteria and protists and comparing those with direct trophic interactions, they demonstrated that specific bacterial volatiles can provide early information about suitable prey. In particular, it was shown that terpenes such as β-Linalool, β-Pinene, Germacrene D-4-ol or δ-Cadinene produced by C. pratensis Ter91 (Song et al 2015b) can stimulate protist activity and motility suggesting that terpenes can be key components in VOCs-mediated communication between protists and bacteria (Schulz-Bohm et al 2017a). Interestingly, soil protists such as Dictyostelium discoideum ) produce volatile terpenes.…”
Section: Protists-bacteriamentioning
confidence: 99%
“…Thus, sensing their prey over long distances in the porous soil matrix would be very beneficial for protists. A recent study by Schulz-Bohm et al (2017a) revealed that volatile organic compounds can play a key role in long-distance bacterial-protists interactions. By testing various volatile-mediated interactions between phylogenetically different soil bacteria and protists and comparing those with direct trophic interactions, they demonstrated that specific bacterial volatiles can provide early information about suitable prey.…”
Section: Protists-bacteriamentioning
confidence: 99%
“…Especially, terpenes were shown to play important roles in the long-range communication between microorganisms (Schmidt et al, 2017, Schulz-Bohm et al, 2017. Arguably, terpenes represent the largest and structurally most diverse class of natural products with over 55,000 members so far described, including monoterpenes, sesquiterpenes, and diterpenes.…”
Section: Introductionmentioning
confidence: 99%